Ultrastructural aspects of the mandibular gland of Melipona bicolor Lepeletier, 1836 (Hymenoptera : Apidae, Meliponini) in the castes - Gracioli, L. F.; de Moraes, RLMS; Cruz-Landim, C. (Elsevier B.V., 2004)
The mandibular gland in Melipona bicolor workers and queens was studied by scanning and transmission electron microscopy. There is no difference in the gland anatomy between the castes, but the transmission electron microscopy showed variation of the cellular ultrastructure according to the secretory phase of the gland in both castes. Smooth endoplasmic reticulum was abundant in the secretory cells of physogastric queens, indicating that these cells produce lipid secretion that is stored in granules with multi-lamellar bodies. Mitochondrial variations during the cell secretory cycle indicates their participation in the lipid synthesis. After secretion, release in the reservoir lumen through the collecting canals, the secretory cells contain many myelinic bodies, indicative of cellular regression. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: mandibular glands; Melipona bicolor; ultrastructure; scanning electron microscopy; transmission electron microscopy